REPRESENTASI SELF-ACCEPTANCE: ANALISIS SEMIOTIKA JOHN FISKE PADA VIDEO KLIP YURA YUNITA "TUTUR BATIN" - Anisa Khairunisa (2023)
Music videos are one of the media used to convey messages. Yura Yunita, an Indonesian musician, wrote a song that invites women to feel their own greatness in imperfection titled "Tutur Batin" (Inner Voice). In the comment section of the "Tutur Batin" music video, many viewers felt the same and cried while watching the video. This research aims to determine the representation of self-acceptance in Yura Yunita's "Tutur Batin" music video based on the level of reality, representation, and ideology. This research uses a qualitative descriptive approach. The method used in this research is John Fiske's semiotics analysis model, namely "The Codes of Television," which has three levels, namely reality, representation, and ideology, which are strengthened through interviews with a clinical psychologist. The final result of this study is that the reality depicted in the music video corresponds to the reality that occurs during the process of self-acceptance, and can represent the process of self-acceptance seen from the components of self-acceptance. The ideological code found in the "Tutur Batin" music video relates to individualism, self-improvement, and self-love ideology.